KONSERVASI BANGUNAN PADA GEDUNG JUANG 45 TAMBUN DENGAN METODE ADAPTIVE REUSE - Nur Falqiyah Miftahul Ilmi; Ayub Muktiono (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
In the history of the struggle for Indonesian independence, Bekasi is nicknamed the City ofPatriots because it cannot be separated from the brave and brave Bekasi fighters. Gedung Juang 45Tambun is one of the symbols of the struggle for the founding of the Republic of Indonesia. This studydescribes one way conservation by using an adaptive reuse strategy. The method used in this researchis qualitative method. In this strategy the building is conserved by transferring its function, wichfunction can be beneficial for the building. From the results of the research, currently the Juang 45building has been converted into a digital museum and not much has changed from the Juang 45building. The benefits that can be felt after the conservation of the Juang 45 Building into a historicaltourist spot in Bekasi Regency is that the community cares more about protecting and preserving the historical heritage of the heroes, increasing tourist attraction, and increasing the economy of the street vendors around the Juang 45 Building.